Concentrations of total N, total P, and gases in an oxygen-deficient upwelling system during El Niño (2019) - Silvia Pajares; Martin Merino; Laura Farías (PANGAEA, 2023)
Seawater samples were collected in four stations along a cross-shore transect in front of the Port of Mazatlán (Mexico) during the oceanographic cruise Maz V (April 2019) on board the R/V “El Puma” (UNAM). Samples were collected at different depths based on the oxygen and chlorophyll-a profiles: surface (5 m depth); mixed layer, deep chlorophyll maximum (at 10–45 m depth); oxycline, base of the oxycline (at 60–125 m depth); upper OMZ; OMZ core (at 250 m depth); and bottom (between 23 m depth in S1 and 670 m depth in S4). Total N and P were determined using a Skalar San-Plus segmented-flow autoanalyzer. Dissolved gases were analyzed through the addition of 5 mL of ultrapure helium into the vials to generate a static-headspace equilibration. N2O was analyzed with a Varian 3380 gas chromatograph using an electron capture detector. CH4 was analyzed with a Schimadzu 17A gas chromatograph with a flame ionization detector and a capillary column.